P. A. Kupriyanov and his work at The First Medical Institute of Leningrad: «With deep insight into the nuances of the chosen specialty» - G. G. Khubulava; V. V. Sizenko; N. G. Luk’yanov; R. A. Akhadov; I. B. Oleksyuk; A. A. Zhuravlyov; I. M. Navaliyev (Учёные записки Санкт-Петербургского государственного медицинского университета им. Акад. И.П. Павлова, 2020)
Since 1926, Peter Andreevich Kupriyanov served at Z.P. Solovyov Central Red Army Military Hospital of Leningrad and simultaneously began to work part-time at Pavlov First Medical Institute of Leningrad. This article talks about the work of P.A. Kupriyanov at The First Medical Institute of Leningrad from 1926 to 1948.